ENHANCING THE STUDENTS’ ENGAGEMENT IN LEARNING ENGLISH ALPHABET BY USING ARPHABET APPLICATION - Zurida Ishak; Wan Auji Qistina Wan Roslan; Rabab Alayham Abbas Helmi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Due to the present COVID-19 health crisis, schools and institutions rushed to introduce online education, which has begun to negatively impact the quality of education for millions of students worldwide. This pandemic has highlighted the necessity to adopt cutting-edge educational technologies, including augmented reality, to enhance the teaching process. The main objective is that researchers want to identify the factors that affect students’ engagement when learning the alphabet using traditional methods. This research aims to enhance the existing traditional method by introducing a new application and learning method to children called ARPHABET, that brings collaboration with Augmented Reality. Students can interact with AR that has an AR marker on it. With the results, the researcher can possibly make improvements to the learning experience and response towards alphabet learning. The researcher conducted interview sessions for teachers and post-test usability tests for a total of 30 children to validate the students’ engagement when using AR for learning. The researcher used Instructional Material Motivation survey (IMMS) questions with the support of the ARCS model. The researcher concluded that the type of learning and contents in the learning application lead to the increase of student’s engagement in learning if the collaboration of augmented reality technology is included in the learning activity.